Analisis Pemberitaan Timnas Indonesia pada Media Daring - Rr. Pramesthi Ratnaningtyas; Yusuf Alawy Muhammad (MUKASI: Jurnal Ilmu Komunikasi, 2023)
This study aims to determine how the online media goal.com and bola.com construct news coverage for the Indonesian National Team Passing the Final Round of the 2023 Asian Cup Qualifications. Football itself is a prevalent sport in Indonesia. The journey of the Indonesian National Team's achievements in the Asian Cup is highly anticipated. The last appearance of the Indonesian national team at the Asian Cup was in 2007. The object of this research news was taken from the Goal and Bola media portals on the 11 - 13 October 2021 edition. This research uses a constructivist paradigm with a qualitative approach and uses the framing analysis model of Zhongdang Pan and Gerarld M Kosicki. The results of the research, goal.com and bola.com, have the same perspective in responding to the Indonesian National Team qualifying for the 2023 Asian Cup qualifying finals. The two media provided support for Indonesia's match against Chinese Taipei. The form of support provided by the two media can be seen from the large amount of news discussing exciting things about the Indonesian National Team, the selection of sources mainly from the National Team, and the number of news headlines that discuss many of the Indonesian National Team.